An Energy Efficient Multicast Routing Protocol for MANET (International Journal of Engineering and Computer Science, 2018)
An important and essential issue for multicast mobile ad-hoc networks (MANETs) is routing protocol design i.e. a major technical challenge due to the dynamism of the network. Mobile Ad-Hoc Network (MANET) is a dynamic, multi-hop and autonomous network composed of light wireless mobile nodes. A lot of control messages are required to build optimal multicast trees and maintaining group membership due to the dynamism of MANETs. Due to these overheads we consume greater energy resourses of mobile nodes and network resourses like wireless links bandwidth . This paper presents an effective multicast routing protocol for MANET with least control overhead. The protocol constructs shared multicast tree using the physical position of the nodes for the multicast sessions. To obtain the physical location of the nodes we use the concept of distributed location service , which effectively reduces the overheads for route searching and shared multicast tree maintenance.In this protocol we use the concept of small overlapped zones around each node for active topology maintenance with in the zone. To pursuit for an existing multicast tree outside the zone, constrained directional forwarding is used which ensure a good reduction in overhead in comparison to network wide flooding for search method.The protocol employs local connectivity technique and protective route reconfiguration on the basis of the current status of the nodes are being proposed which reduces the overhead, power and bandwidth requirement and try to increase the performance and reliability.